Tight binding description on the band gap opening of pyrene-dispersed graphene - Chen, Dongmeng (2011)
Opening up a band gap in graphene holds a crucial significance in the realization of graphene based electronics. Doping with organic molecules to alter the electronic properties of graphene is perceived as an effective band gap engineering approach. Using the tight binding model, we examined the band gap opening of mono layer graphene due to the adsorption of pyrene molecules on both of its sides. It was found that the breakdown of the sublattice symmetry in pyrene-dispersed graphene leads to a band gap of ~10 meV.